PENGARUH PERSEPSI TENTANG BUDAYA ORGANISASI TERHADAP KINERJA INDIVIDU PADA KARYAWAN PUSKESMAS KARANGDOWO KABUPATEN KLATEN - setyawan, anita agustina (MOTORIK Jurnal Ilmu Kesehatan (Journal of Health Science), 2011)
In the global and free trade era, competence, qualified as well as competitive human resources are highly needed by an organization. Therefore an organization culture and individual performance staff at Karangdowoâs Public health center be improved to give excellent service to the public. The research aimed to know about perceptionâs influence about organization culture within individual performance on KarangdowoâsÂ  public health at Klaten residence and how the influence of organization culture type within individual performance on KarangdowoâsÂ  public health at Klaten Residence. This research used a descriptive method. It was conducted by distributing questionnaires to 56 staff as population. Descriptive analysis use statistical with product moment correlation to know influence of organization culture within individual performance staff. Result of this research show a significant an influence about four organization culture types clan culture, adhocracy culture, hierarchy culture, and market culture within individual performance on KarangdowoâsÂ  public health at Klaten Residence. Staff characteristic like: age, gender, work period, state of work, and state of staff havesignificant influence withn individual performance on Karangdowoâs public health at Klaten Residence. This research prove that age, gender, work period, and state of work, and state of staff influence performance of workman. Â  Keyword: organization culture, individual performance, staff characteristic.